TRANSFORMASI DIGITAL MUSEUM NASIONAL INDONESIA MELALUI IMERSIFA DAN MENGENAL PARAS NUSANTARA UNTUK EDUKASI GENERASI ALPHA - Amanda Olivia; Prayogo Susanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The objective of this study is to analyze the digital transformation of National Museum of Indonesia through ImersifA and Mengenal Paras Nusantara as educational media for Generation Alpha. The background of this study stems from the rapid advancements in digital technology, therefore prompted museums to devise an educational experience that is more interactive, immersive, and resonating with the characteristics of Generation Alpha as a digital native. National Museum of Indonesia is a notable institution within the Indonesian museum landscape, having adopted digital technology as a means to enhance its educational mission through the integration of visual and interactive technologies. This study employs a descriptive qualitative methodology. The data were collected through observation, interviews, documentation, and literature study. The informants comprised of museum management staff, student visitors from Generation Alpha, and a teacher. The data were then subjected to analysis that entailed data reduction, data presentation, and conclusion drawing. The findings indicate that ImersifA and Mengenal Paras Nusantara effectively generate a more interesting and relevant learning experience for students from Generation Alpha. ImersifA provides an immersive learning experience through audio-visual presentations from 360 angle video mapping technology, meanwhile Mengenal Paras Nusantara offers a more personalized interaction through face scanning technology with the usage of artificial intelligence. Both of the services support the educational approach with constructivism theory that matches well with the characteristics of Generation Alpha. This study also identifies challenges in managing digital services, especially regarding challenges in technical operations, human resource readiness, and complicated bureaucracy. The digital transformation of National Museum of Indonesia can enhance museum’s role as an adaptive public educational space in the digital era.